2012
DOI: 10.4236/ijcm.2012.37a132
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Fasting-Evoked en Route Hypoglycemia in Diabetes (FEEHD): A Case Series Study

Abstract: <p class="MsoNormal"> <b><span lang="EN-US">Background: </span></b><span lang="EN-US">A recent study reported that some patients with diabetes who fast overnight for laboratory tests are at risk of developing hypoglycemia, which could occur while patients are in risky situations which could result in harm to pa</span><span lang="EN-US">tients or others. Due to limitation in study design of the aforementioned study, the causes of hypoglycemia could not be elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 14 publications
(29 reference statements)
1
12
0
Order By: Relevance
“…Whereas patients who are not taking hypoglycemic medications (i.e., insulin and insulin secretagogues) are protected by a complex physiological response that inhibits insulin production by the beta cells during fasting, patients taking such medications typically do not have such a protective mechanism in view of continued circulating insulin [10]. This risk is further aggravated in patients with long-standing diabetes due to the loss of additional counter-regulatory mechanisms that protect from hypoglycemia during fasting, i.e., glucagon and catecholamines [12]- [15].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Whereas patients who are not taking hypoglycemic medications (i.e., insulin and insulin secretagogues) are protected by a complex physiological response that inhibits insulin production by the beta cells during fasting, patients taking such medications typically do not have such a protective mechanism in view of continued circulating insulin [10]. This risk is further aggravated in patients with long-standing diabetes due to the loss of additional counter-regulatory mechanisms that protect from hypoglycemia during fasting, i.e., glucagon and catecholamines [12]- [15].…”
Section: Introductionmentioning
confidence: 92%
“…As recently reported, patients with diabetes on hypoglycemic medications are especially vulnerable to fasting that can increase their risk for hypoglycemia especially if they are not adequately prepared for fasting [10]- [12]. Specifically, patients with diabetes who use insulin or sulfonylureas are put at increased risk for hypoglycemia when fasting [10]- [13].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…4 Another case series elaborated further on the causes of this newly recognized form of hypoglycemia, depicting a series of cases of diverse demographic and clinical presentations. 5 These recent reports emphasized the seriousness of hypoglycemia induced in patients with diabetes mellitus who are asked to fast overnight for lipid testing. [3][4][5] Overnight fasting is often requested in a routine manner, at least annually in this patient population.…”
Section: To the Editormentioning
confidence: 99%
“…[3][4][5] A recent pilot study 3 demonstrated an increased risk of hypoglycemia in patients who fast for laboratory tests if such patients are not well informed about adjustment of their antidiabetic medications (ie, insulin and sulfonylureas). In another study, the same authors reported a practice that almost completely eliminated the fasting prerequisite for lipid testing.…”
Section: To the Editormentioning
confidence: 99%